2008
DOI: 10.1203/pdr.0b013e31817cfca6
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Markers of Oxidative DNA Stress, RNA Degradation and Protein Degradation Are Differentially Correlated With Resting Metabolic Rate and Energy Intake in Children and Adolescents

Abstract: Urinary excreted RNA and DNA catabolites are used as noninvasive markers for metabolic processes: 8-oxo-2'-deoxyguanosine (8-oxodG) potentially represents oxidative stress to DNA/deoxyribonucleotidetriphosphate pool, modified ribonucleoside pseudouridine (psi) originating mainly from degraded rRNA and tRNA reflects RNA turnover. Modified amino acid gamma-carboxyglutamic acid (Gla) stems from degraded proteins reflecting turnover of proteins. Aim of the present study was to investigate (44 healthy males, 3-18 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 45 publications
1
18
0
Order By: Relevance
“…In the present study, TBARS had independent association with BRS in obese group subjects (Table 5). From the findings of the present study, it appears that increased oxidative stress in obese subjects could be due to the increased sympathetic drive and increased BM, as there are earlier reports of oxidative stress in conditions of increased sympathetic activity and metabolism [45,46]. Thus, oxidative stress could be the possible link between increased BM and decreased BRS in obesity.…”
Section: Discussionsupporting
confidence: 76%
“…In the present study, TBARS had independent association with BRS in obese group subjects (Table 5). From the findings of the present study, it appears that increased oxidative stress in obese subjects could be due to the increased sympathetic drive and increased BM, as there are earlier reports of oxidative stress in conditions of increased sympathetic activity and metabolism [45,46]. Thus, oxidative stress could be the possible link between increased BM and decreased BRS in obesity.…”
Section: Discussionsupporting
confidence: 76%
“…These metabolic processes, again, could be targeted by oxidative DNA stress in pediatric obesity and obesity-related NAFLD, in conditions such as high dietary energy intake [42]. …”
Section: Discussionmentioning
confidence: 99%
“…Kim et al (Kim et al, 2010) and studies cited therein]. Interestingly, in non-reproducing females, the level of oxidative damage was higher in L-BMR mice, whereas earlier studies reported positive inter-and intra-specific correlation between the concentration of 8-oxodG and basal and/or standard metabolic rate (Foksinski et al, 2004;Topp et al, 2008).…”
Section: Discussionmentioning
confidence: 87%